The Value of Crime Scene and Site Visitation by Forensic Psychologists and Psychiatrists - Mohandie, Kris; Meloy, J. Reid (Journal of forensic sciences, 2013)
Site visits and crime scene visitation by forensic psychologists and psychiatrists may enhance the accuracy and credibility of their forensic work in criminal, civil, and other important contexts. This ethically sound technique of after‐the‐fact data collection and verification offers numerous potential benefits to the forensic mental health professional: clarifying the subject's actions, assessing the reliability of witness reports, identifying contextual determinants of behavior, and more fully illuminating subject motivation and decision‐making. Limitations and suggested guidelines for conducting site visits are offered. Guidelines include preplanning, arranging for an informed guide to accompany and narrate the visit, and conducting the site visit prior to forensic examinations.